PENELUSURAN BANJIR KOLAM RETENSI SUSUKAN KECAMATAN UNGARAN TIMUR KABUPATEN SEMARANG - Anita Khairul; Diyah Fatmawati; Ratih Pujiastuti; Totok Apriyanto (Jurnal Teknik Indonesia, 2023)
Floods are natural disasters that occur in an area due to the inability of drainage channels or many rivers, in overcoming the flooding problem that occurred a problem that occurred in, Susukan District, East Ungaran District, the Semarang Regency Government has taken action by constructing a retention pond. This research aims to analyze the capacity of the retention pond.This research required data: topographic data, rainfall data and geotechnical soil data. The analysis carried river watershed and hygrological analysis which includes: determining average rainfall, planned flood discharge, flood routing and calculating the stability of the spillway building.From the results of the hydrological analysis, the flood discharge value obtained using the gamma I unit hydrograph method for a 5-year return period was 21,53 m3/second. In flood investigations, an outflow value of 21.11 m3/second was obtained with an overflow height of 1,65 m.